COMPETITIVENESS ESTIMATION OF FRUIT AND VEGETABLE ENTERPRISE COMPANIES OF THE REPUBLIC OF KAZAKHSTAN - Wei Peng , (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses the activities of enterprises associated with the fruit and vegetable industry. The role of this enterprise is great because it is associated with the production, as well as with the manufacturing industry. An assessment was made of threats to key industry players. The most effective method of dealing with substitutes is to build a strong brand: a clear differentiation and additional benefits from the consumption of company goods, the fight against product standardization, technological improvements, the formation of product loyalty. Competition among existing competitors is reduced to the desire to improve their position in the market by any means in order to conquer the consumer market. Intense competition leads to price competition, increased costs for the promotion of goods, sometimes to improve product quality, increase investment in new developments. All this reduces the profitability of the industry. This approach includes five competitive forces: the power of consumers, the power of suppliers, the potential of new participants in the industry, the threat of substitute products, and competition in the industry. A table was created for evaluating assessment results for organizations in the industry. Developed proposals for the strategic development of enterprises in the industry.